Predictive Factors Associated with Inappropriate Intravenous Proton Pump Inhibitors Use in Hospitalized Patients: A Case-Control Study - Niveen Khoury; David Stepensky; Naim Abu Freha; Mahmud Mahamid; Tawfik Khoury; Amir Mari (Medicina)
Background and Objectives: Proton Pump Inhibitors (PPIs) are the most effective agents for treating acid-related gastrointestinal disorders. The prescription of an intravenous (IV) formulation of PPIs has increased dramatically. The aims of this study were to assess the appropriateness of IV PPI use and to define the risk factors and outcomes associated with its inappropriate use. Materials and Methods: A case-control retrospective study included all the hospitalized patients who received IV PPIs was conducted. Patient health records were reviewed, data were collected covering the period of the individual patients’ admission to the hospital until discharge or death, and over the 3-month post-discharge period. The appropriateness of the IV PPI use and the resulting clinical outcomes were analyzed. Results: Overall, 540 patients were analyzed. Among them, 130/540 (24%) had inappropriate PPI use in terms of indication, dosage, and duration of treatment vs. 410 patients who had appropriate indications. Two parameters were associated with inappropriate use: congestive heart failure (OR 1.77; p = 0.02) and prescription of IV PPIs by surgeons vs. internists (OR 1.53; p = 0.05). Conclusions: Inappropriate IV PPI use is still common in daily clinical practice. Significant predictors of inappropriate use were the presence of congestive heart failure, elderly age, current use of anticoagulants and antithromotics, and the cases managed by surgeons, naturally due to suspected upper gastrointestinal bleedings.